2004
DOI: 10.1007/s00467-004-1691-x
|View full text |Cite
|
Sign up to set email alerts
|

Serum VCAM-1, ICAM-1, and L-selectin levels in children and young adults with chronic renal failure

Abstract: Children and young adults with chronic renal failure (CRF) present with an impaired immune response. Our aim was to analyze whether leukocyte migration, determined by adhesion molecules, is disturbed in the course of CRF, hemodialysis (HD), and peritoneal dialysis (PD). Soluble (s) VCAM-1, ICAM-1, and L-selectin serum levels were evaluated by ELISA in 15 patients with CRF, 22 patients on cuprophane membrane HD, 24 patients on PD, and in 15 controls. The sVCAM-1 levels in all groups were significantly elevated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
2
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 23 publications
2
21
2
3
Order By: Relevance
“…Interestingly, sVCAM-1 might be related to certain blood infections in HD patients [17], however, the increase of its serum levels was rather moderate, well below the highest increases in our study. The increased level of sE- and sP-selectin in HD patients in our study is consistent with other reports [6, 14, 18]. …”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Interestingly, sVCAM-1 might be related to certain blood infections in HD patients [17], however, the increase of its serum levels was rather moderate, well below the highest increases in our study. The increased level of sE- and sP-selectin in HD patients in our study is consistent with other reports [6, 14, 18]. …”
Section: Discussionsupporting
confidence: 83%
“…The concentration of sVCAM-1 was commonly found increased in CRF patients on peritoneal dialysis or HD [5, 14]. Contrary to our results, the levels of sVCAM-1 were found increased both in pre-dialysis CRF patients and during dialysis [6], while the concentrations of the adhesion molecules sVCAM-1 and sICAM-1 were raised in CRF patients compared to the control group [15].…”
Section: Discussioncontrasting
confidence: 55%
“…(33,34) According to M. Zwolinska, in this condition, the synthesis of VCAM-1 is enhanced, triggering several reactions that cause endothelial dysfunction. (35) When measuring serum TnT, we found that in patients with BPV Type 1, TnT level ranged between 0.1 ng/ml and 0.3 ng/ml (0.23±0.12 ng/ml), whereas in patients with other types of BPV, TnT level did not exceed the upper reference limit. This fact indicates a more significant lesion of the myocardium as a target organ in AH patients with BPV Type 1, which is associated with an unfavorable cardiovascular prognosis.…”
Section: Resultsmentioning
confidence: 75%
“…Leukocyte inflammatory responses are based on leukocyte attachment to the endothelium mediated by adhesion molecules such as integrins, selectins and molecules from the immunoglobulin superfamily (ELAM-1, ICAM-1 and VCAM-1) determining subsequent stages of the adhesion cascade [23, 24]. The predominant mechanism of interaction at normal shear rates involves sequential participation of selectins and integrins, whereas at low shear rates adhesion can be supported solely through integrin and ICAM-1.…”
Section: Discussionmentioning
confidence: 99%